Square beak - Sun, Chyng Feng (Houghton Mifflin Company, 1993)
The story is about a chicken and her exploration and dreaming of places throughout the day, activities that cause her to lay rainbow-colored eggs that reflect the landscapes she has seen. This uncanny ability boosted her popularity for a while, until she agreed to represent others in an egg-laying competition, realizing that the confinement it entailed was limiting. her creativity and stopped collaborating, returning to her solitary but satisfying wanderings.